METHODOLOGY OF EDUCOLOGY: SYNERGETIC ASPECT - Batechko, Nina H. (Educological discourse, 2017)
In the article the author ponders over the role and importance of theory of synergetics in methodology of educology. Modern education sector has been considered as a complex, open, non-linear, non-equilibrium system capable of self-organization. The phenomenon of self-organization is studied as a possible direction of modernization of education in Ukraine.